Internalization of Shigella flexneri into HeLa cells occurs without an increase in cytosolic Ca2+ concentration. - Clerc, P L (1989)
Pathogenic Shigella flexneri invades epithelial cells through directed phagocytosis. The role of intracellular free calcium ([Ca2+]i) as a signal for this process was tested. No variation in the [Ca2+]i could be detected by using the fluorescent indicator fura 2 to measure the [Ca2+]i in HeLa cells during the invasion process. In addition, neither clamping nor maximal decreasing or increasing of the [Ca2+]i of HeLa cells had any effect on their susceptibility to invasion. These data demonstrate that [Ca2+]i is not a signal for S. flexneri directed phagocytosis in HeLa cells.